An Aerial Base Station Assignment Algorithm for 5G Networks - Reis, Renata K. G. dos; L. Damasceno, Maria G.; A. Arnez, Jussif J.; B. de Souza, Caio B.; M. Balieiro, Andson (Anais do Workshop de Redes 6G (W6G); 2025: Anais do V Workshop de Redes 6GDO - 10.5753/w6g.2025.9284, 2025)
Due to network capacity and coverage demands of existing 5G and Beyond 5G networks, Aerial Base Stations (ABS) based on Unmanned Aerial Vehicles (UAV) have been highlighted as a key strategy to expand terrestrial network and assist mobile users. Nevertheless, ABS based on UAV (UAV-BS) are resource constrained in comparison to terrestrial base stations, which implies that resource management procedures are required to efficient UAV-BS operation. In this respect, this work proposes a clustering-based user assignment solution for user to UAV-based ABS, employing a reallocation approach for avoiding connection denial, evaluating the average of allocated users and throughput.